Financing decision: A vital key to explaining small and medium enterprises (SMEs) financial performance - Katerega, Yusuf N.; Ngoma, Mohamed; Masaba, Ayub K.; Nangoli, Sudi; Waswa, Yusuf; Namiyingo, Sophie (Journal of Economics and International Business Management, 2015)
This research focuses on financing decisions as a predictor of financial performance of small and medium size enterprises in Mbale District in Uganda. The study adopted a cross sectional survey involving a sample size of 341 SMEs in the categories of General merchandise, super markets, manufacturing, hotels and restaurants. Simple random sampling was used to select the 341 firms from the total population of 3,274 firms as the unit of analysis, the owners and senior staff were the unit of inquiry. One respondent was targeted per firm. Results of the multiple regression analysis revealed a significant positive relationship between financing decision of SME‟s and their financial performance, implying that financing decision is a significant predictor of financial performance of SMEs in Uganda. As small and medium enterprises continuously search for ways of improving their financial performance they should pay particular attention to professionalism and interest rates in their quest to boost financial performance.
Keywords: Financial performance; Financing decision; Small and medium enterprises; Strategy